Life expectancy and human capital investment: the arrival of AIDS treatment in Brazil - Matos, Victor Chagas (2016)
This paper provides microevidence on the relationship between life expectancy and educational investment decisions. Human capital theory predicts an increase in life expectancy should lead to an augmenting in schooling investment. This paper uses an unique data set on AIDS patients among Brazilian inhabitants in an attempt to estimate the impact of the arrival of Antiretroviral therapy (ART) on educational outcomes. The availability of ART offsets the negative relationship between vertical HIV-transmission and schooling, around 68% and 57% for elementary and high school completion, respectively. Robustness tests indicate the results are not driven by convergence effects.